Amasa J. Parker papers - Parker, Amasa J. (Amasa Junius), 1807-1890.
Chiefly letters written by Parker while serving in the U.S. Congress to his wife, Harriet Langdon Roberts Parker, in Delhi, N.Y., describing his trip to Washington, the city, the Capitol building, and his impressions of John Quincy Adams, John C. Calhoun, and Daniel Webster. Other topics include dueling, Indian affairs, politics, and Washington social life and theater. Also includes letters written while Parker was a lawyer in New York State and a newspaper illustration (1875) announcing his candidacy for the U.S. Senate from New York.
In part, typewritten transcripts.
Lawyer, judge, and U.S. representative from New York.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John Quincy, -- 1767-1848.; Calhoun, John C. -- 1782-1850.; Parker, Harriet Langdon Roberts -- Correspondence; Webster, Daniel, -- 1782-1852.; United States. -- Congress; United States. -- Congress. -- Senate -- Elections, 1876.; United States Capitol (Washington, D.C.); Dueling -- United States; Indians of North America -- Government relations; Practice of law -- New York (State); Theater -- Washington (D.C); Delhi (N.Y.) -- History; New York (State) -- Politics and government -- 1775-1865.; United States -- Politics and government -- 1837-1841.; Washington (D.C.) -- Description and travel; Washington (D.C.) -- Social life and customs; Jurists; Lawyers; Representatives, U.S. Congress -- New York (State)